The impact of immigration on the labour market outcomes of native-born Canadians - Jiong Tu (Institute for the Study of Labor (IZA), 2010)
Although immigration has become a major growth factor for Canadian labour force, there is little economic research on the effect of immigration on native-born Canadians' labour market performance. This paper examines the relationship between changes in the share of immigrants by sub-labour markets (categorized by skill types and geographic areas) and changes in native wage growth by a two-stage regression analysis, using 1991, 1996 and 2001 Canadian Census data files. After accounting for biases due to native mobility, endogenous location of immigrants and labour demand shifts, the estimated effects of immigration are consistently insignificant or significantly positive. The results are robust to various specifications of sub-labour markets at city, provincial and national levels, suggesting that there is no evidence for a negative impact on native wage growth rate from the large immigrant influx during the 1990s.
urn:nbn:de:101:1-201010132847
Keywords: F22; J15; J31; J61; 330; immigrant; wages; labour market; Canada